Spittlebug Cephisus siccifolius damaging eucalypt plants in the State of Bahia, Brazil - Ribeiro, Genésio Tâmara; Mendonça, Marcelo da Costa; de Mesquita, João Basílio; Zanuncio, José Cola; Carvalho, Gervásio Silva (Pesquisa Agropecuaria Brasileira, 2005)
Most common pests of eucalyptus plants in Brazil are leaf cutting ants and defoliating caterpillars. Other groups, eventually, feeding on eucalyptus include Heteroptera and cicadas. The objectives of this work were to identify and to describe attack symptoms of Cephisus siccifolius (Walker 1851) (Hemiptera: Aphrophoridae) on eucalyptus trees in a stand of 25.77 hectares in the State of Bahia, Brazil, where 99.3% of them were attacked by this spittlebug. Damage was more severe on branches and leaves. Tree death was, relatively, low while those cut showed 4.7 colonies of this spittlebug with 21.9 nymphs per colony. Cultural control with the removal of trees attacked was recommended.